One new species and one new record of the genus Trirogma Westwood (Hymenoptera: Ampulicidae) in China, with a key to the world species - Liu, Zhi-Zhi; Ma, Li; Li, Qiang (Zootaxa, 2024)
The taxonomy of the genus Trirogma from China is studied, with description of one new species from Guangdong and Yunnan Provinces in China, namely Trirogma lobusicurvus Liu et Li, sp. nov. Meanwhile, one newly recorded species, Trirogma kohima Girish Kumar and Sheela, 2018 from China is reported and the female is described for the first time. An updated key to the world species of Trirogma is provided.